“Like dissolves like” enables the synergy of fluorinated additive and fluorous solvent soaking for high-performance organic solar cells - Zhilong He; Shimin Zhang; Siyuan Li; Zhe Hao; Yan Chen; Hongliang Zhong (Materials Today Advances)
The pre-treatment and post-treatment of organic solar cells (OSCs) are two important device engineering processes that are closely associated with photovoltaic performance. Yet these two stages are independently developed to optimize the morphology and then improve the device performance, while their synergy is believed to be more productive. In this study, the fluorinated additive and fluorous solvent soaking (FSS) are simultaneously employed in OSCs, and the “like dissolves like” concept drives their synergetic role on the morphology optimization. The fluorinated additive 1,8-diiodoperfluorooctane (FDIO) could selectively enhance the packing order and crystallinity of the acceptor through forming the fluorine-induced interactions. Moreover, fluorous solvent could penetrate into the blend film and then remove the residue FDIO while further optimizing the morphology by enhancing molecular packing. By employing the synergy of FDIO additive and FSS treatment (40 °C for 30 s), a champion power conversion efficiency (PCE) of 18.64 % with the simultaneous improvements of photovoltaic parameters is achieved. This study provides a synergetic strategy by employing fluorinated additive and fluorous solvent to tune film morphology in the film-formation and post-treatment processes, respectively, consequently advancing the photovoltaic performance of OSCs.